Technological Advance and the Labour Share of National Income in the European Union - Briguglio, Lino; Vella, Melchior (Journal of Income Distribution®, 2016)
This article tests the hypothesis that member states of the EU have been experiencing a declining share of labour income due to technological advance. It discusses factors that lead to the fall in the labour share, including technological advance, which is a tendency found in the capitalist system. We also identify the undesirable effects of a fall in the labour shares. The results of an econometric test conducted in our study, based on a labour demand equation that was derived from the CES production function, confirm the hypothesis that technological progress negatively affected the labour share of income, everything else remaining constant. This finding has important implications for EU Member States, namely that some form of policy intervention would seem to be necessary, as technological progress could lead to a continuing fall in the share of labour income if left to its own devices.